Facebook as Tool of Marketing in the Era of Digital Marketing - B. Valand, Jignesh; Gaur, Ashok (International Journal of Psychosocial Rehabilitation, 2020)
Facebook was introduced as a social network for college students, but today in this digital age, it is used nearly by everyone with an internet connection and is used by all other age groups. It has turned out to be the globe’s largest social network. Facebook has billions of daily online users. The tools of Facebook are in the form of Facebook Pages, Facebook Advertisement and Publicity, and Facebook Groups. This can be used to promote products, services, organizations, events, and many more. Each of these tools can be used for different purposes according to requirement, or all can be used at the same time for better results. Facebook marketing means creating and actively using a Facebook for market and marketing-related activities and for the purpose of interacting and maintaining contact with and attracting customers. This research article is about how Facebook can be used as a tool for marketing business on the world’s largest social network.